Kaj pa pop? - Stanković, Peter (Družboslovne razprave, 2013)
The history of Slovenian popular music is one of the most under-researched areas of Slovenian cultural heritage. It can be argued, therefore, that no definitions of Slovenian popular music would have been established had extensive research not been carried out by different scholars and experts, functioning in this respect as a kind of substitute for official work. The question here is simply what kind of understanding of Slovenian popular music emerges in this more or less spontaneous and unofficial research. The author analyses the content of all Slovenian scientific and expert monographs, scientific and expert articles, film and TV documentaries as well as school textbooks, at least some segments of which address Slovenian popular music, and argues that these accounts are significantly biased: for the most part, they focus only on different marginal music genres while the majority of other music genres, including all those that are the most popular among Slovenians, are neglected.
Keywords: Popular music; Volkstümliche Musik; Zabavna glasba; Zgodovina; History; Kulturna dediščina; cultural heritage; Cultural property; Glasba; Music; Slovenia; Slovenija; popularna glasba